2019
DOI: 10.3389/fmicb.2019.00741
|View full text |Cite
|
Sign up to set email alerts
|

O-Antigen Gene Clusters of Plesiomonas shigelloides Serogroups and Its Application in Development of a Molecular Serotyping Scheme

Abstract: Plesiomonas shigelloides is a Gram-negative, flagellated, rod-shaped, ubiquitous, and facultative anaerobic bacterium. It has been isolated from various sources, such as freshwater, surface water, and many wild and domestic animals. P. shigelloides is associated with diarrheal diseases of acute secretory gastroenteritis, an invasive shigellosis-like disease, and a cholera-like illness in humans. At present, 102 somatic antigens and 51 flagellar antigens of P. shige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The comparison of the O-AGCs of a total of 11 serotypes indicates that the O-AGC of R. anatipestifer is conserved at both ends and variable in the middle region (Figure 8). Similar phenomena also appeared in Plesiomonas shigelloides (Xi et al, 2019), Escherichia albertii (Wang et al, 2017b), and Yersinia pseudotuberculosis (Kenyon et al, 2017). Variations in the O-AGCs often mean differences in the O-antigen oligosaccharide unit and affect the serological phenotype.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The comparison of the O-AGCs of a total of 11 serotypes indicates that the O-AGC of R. anatipestifer is conserved at both ends and variable in the middle region (Figure 8). Similar phenomena also appeared in Plesiomonas shigelloides (Xi et al, 2019), Escherichia albertii (Wang et al, 2017b), and Yersinia pseudotuberculosis (Kenyon et al, 2017). Variations in the O-AGCs often mean differences in the O-antigen oligosaccharide unit and affect the serological phenotype.…”
Section: Discussionsupporting
confidence: 55%
“…wzy , wzx etc.) have been widely used as targets for molecular serotyping of many gram-negative bacteria(Fang et al, 2016; Iguchi et al, 2020; Townsend et al, 2001; Wang et al, 2017a; Xi et al, 2019; Zeng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the genetic diversity and pathogenic potential of P. shigelloides , we generated draft genome sequences for 12 strains representing different serogroups whose O-antigen gene clusters have been reported previously ( 18 ). Phylogeny was performed for a larger collection of the members of Enterobacterales , focusing on the phylogenetic position of P. shigelloides and species-specific genetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…P. shigelloides O17, which carries the same O-antigen as Shigella sonnei , was used in vaccine production against shigellosis [ 7 ]. Our previous study reported the diversity of P. shigelloides O-antigen gene clusters, and also established an identification and detection method for molecular serotyping [ 8 ]. The variability of the O-antigen provides the primary basis for serotyping schemes for P. shigelloides [ 9 ].…”
Section: Introductionmentioning
confidence: 99%